Balanced scorecard adoption: the case of the Milan TA team at BNP Paribas - Zonta, Marco (2016)
This Work Project, written in the form of a Direct Research, is to develop a Balanced Scorecard (BSC), specifically designed for the Milan Transfer Agent (TA) Team of BNP Paribas Securities Services (BP2S), located in Warsaw. The goal is not to focus on the whole company, but to identify the main characteristics of the aforementioned team and to develop the BSC that suit it the most, according also to the strategy given by the corporation. As for all the BSC implementations, the purpose is to balance long-term goals, stemming from the corporate strategy and competitive advantage needs, and short-term objectives.